Analisis Total Productive Maintanance Dengan Menggunakan Metode OEE dan FMEA Pada Mesin Extruder GW – 350 Produksi Roll Sheet - Dodi Marcus Siagian; Deri Teguh Santoso (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2022)
A company engaged in plastic specialists, with the basic ingredients of PolyEthylene Terephthalate, PolyPropylene, and Hight Impact Polystyrene. Products operated by Extruder machines. Total Productive Maintenance (TPM) with Overall Equipment Effectiveness (OEE) and Failure Mode and Effect Analysis (FMEA). Availability, Performance, Rate of Quality and OEE of Extruder GW-150. Based on the quantitative analysis of the OEE calculation, the OEE value of the Extruder 1 GW-350 machine is obtained with an average calculation of 79.35%. Based on the qualitative analysis using FMEA, the RPN failure mode score on the Extruder 1 GW-350 engine was obtained. The highest RPN value is the unstable (die) printer of 240.